Pengaruh Ukuran Butir Kapur Berbeda terhadap pH, Fe-larut dan Al-tukar Tanah pada Lahan Pasang Surut - Akhmad Fauzi; Muhammad Mahbub; Syaifuddin Syaifuddin (Department of Soil, Faculty of Agriculture, Lambung Mangkurat University, 2023)
Swampland in Indonesia covers an area of ​​34.93 million ha spread over various islands such as Sumatra, Java, Kalimantan, Sulawesi, and Papua. One type of swamp land that is often used in agriculture is tidal lands. The problems faced in the development of tidal lands for agriculture include acidic soil pH, high levels of soluble Fe and Al. One of the efforts to overcome the problem of acidic soil pH, high levels of soluble Fe and Al-dd is liming. The finer grain level of lime may increase the effectiveness of liming. The purpose of this study was to quantify the effect of lime grain sizes on changes in pH, dissolved Fe, and exchangeable Al of tidal lands. This study employed a one-factor completely randomized design (CRD) consisting of 6 treatments (Control; CaCO3 more than 1.00 mm (> 18 mesh); CaCO3 lime, 0.5-100 mm (18 -35mesh); CaCO3 measuring 0.21-0.50 mm (35-70 mesh); CaCO3 measuring 0.21 mm (<70 mesh); CaCO3 lime measuring 0.15-1.00 mm (18 -100 mesh)). The results showed that the difference in the size of the CaCO3 lime granules had a significant effect on changes in pH, soluble Fe and exchangeable Al. The application of CaCO3 lime granules 0.21 mm (<70 mesh) result in increases in soil pH and suppress soluble Fe and exchangeable Al.